2020
DOI: 10.33061/jasti.v15i4.3746
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor Yang Mempengaruhi Pelaporan Keuangan Perusahaan Melalui Internet

Abstract: The purpose of this study is to analyze the effect of firm size, profitability, liquidity, and new shares offering to internet financial reporting. The samples used in the study were 114 manufacture companies listed on the Indonesia Stock Exchange in 2018 with proportional stratified sampling method. The analytical method used is logistic regression. The result of this study indicate that the variable new shares offering significant and positive impact to internet financial reporting, while other variables fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
1
5
1
4
Order By: Relevance
“…Research conducted by Idawati and Dewi (2017) and Angela (2021) is in line with research conducted by Kurniawati (2018) which provides evidence that profitability positively affects internet financial reporting. This is different from the research conducted by Ardiastuti et al, (2019) which proves that profitability negatively affects internet financial reporting.…”
Section: Preliminarycontrasting
confidence: 97%
See 2 more Smart Citations
“…Research conducted by Idawati and Dewi (2017) and Angela (2021) is in line with research conducted by Kurniawati (2018) which provides evidence that profitability positively affects internet financial reporting. This is different from the research conducted by Ardiastuti et al, (2019) which proves that profitability negatively affects internet financial reporting.…”
Section: Preliminarycontrasting
confidence: 97%
“…The size of the company is everything owned by the corporation that is used to illustrate the size of the corporation [17]. Firm size can be measured using the logarithm (Ln) of total assets [5].…”
Section: Company Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that liquidity did not affect the completeness of Internet Financial Reporting (IFR) information, this result was in line with previous studies that found that liquidity did not affect IFR (Christ, 2017;Mahendri & Irwandi, 2017;Putri & Setiawan, 2022). This research is different from the results of research conducted by Marwati, (2016) which states that liquidity has a positive effect on IFR.…”
Section: The Effect Of Liquidity On the Completeness Of Internet Fina...supporting
confidence: 77%
“…Menurut Jones et al, (2003) dalam Chariri (2007) internet merupakan alternatif baru dalam pelaporan keuangan yang biasa dikenal dengan internet financial reporting, selanjutnya disingkat IFR. IFR merupakan salah satu komponen praktik pengungkapan sukarela (Ashbaugh et al, 1999).…”
Section: Pendahuluanunclassified